Invasion of the bucco-mandibular space by oral squamous cell carcinoma: histopathological analysis of invasion pattern - Kugimoto, Takuma; Nishii, Naoto; Oikawa, Yu; Kuroshima, Takeshi; Hirai, Hideaki; Tomioka, Hirofumi; Michi, Yasuyuki; Kayamori, Kou; Sakamoto, Junichiro; Iwanaga, Joe; Tubbs, R. Shane; Ikeda, Tohru; et al. (Frontiers in Oncology, 2023)
Background This study aimed to determine the patterns of invasion of oral squamous cell carcinoma (OSCC) into the bucco-mandibular space (BMS) using detailed histopathological analysis and to assess clinical outcomes. Methods Patients with OSCC who underwent segmental mandibulectomy or hemi-mandibulectomy combined with resection of the BMS between 2012 and 2021 were included. The invasions of the BMS were classified into three patterns. Pattern A was defined as a horizontal invasion, Pattern B as a vertical invasion, and Pattern C as an expansive invasion. Results In total, 109 patients were reviewed. Of these 109 patients, the primary tumor affected the lower gingiva in 78 patients, the buccal mucosa in 18 patients, and was a primary intraosseous carcinoma of the mandible in 13 patients. Invasion of the BMS was significantly associated with a higher pathological T stage, positive/close margins, and lower disease-free survival (DFS) rates. The DFS rates were 86.7% and 66.0% in the BMS non-invasion and invasion groups, respectively. The DFS rates for each type of invasion were 82.1% for Pattern A, 67.4% for Pattern B, and 48.0% for Pattern C (P=0.277). Conclusion Patients with BMS invasion have a poorer prognosis than those without invasion of the BMS. Therefore, adjuvant therapy is necessary, especially in Patterns B and C. Evaluation of preoperative BMS invasion patterns is important for predicting the prognosis of OSCC.